Leukemic manifestation of blastic plasmacytoid dendritic cell neoplasm: laboratory approaches in 2 cases - Park, Sang Hyuk; Chi, Hyun-Sook; Cho, Young-Uk; Jang, Seongsoo; Park, Chan-Jeoung (Blood research, 2014)
KCI Citation Count: 0